2007 IEEE International Conference on Automation Science and Engineering 2007
DOI: 10.1109/coase.2007.4341698
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Modeling and Simulation of Health Care Systems

Abstract: International audienceTo remedy lacks in modeling and analysis of health care flow, we present in this paper a new modeling methodology for addressing organization problems of health care systems. It is a patient-centered meta-model based on three views : (i) process (pathway of patients), (ii) resource (activity of involved resources), and (iii) organization (resources relations and specializations, structure of the system). These personalized view are a powerful communication tool. The resulting meta-model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…After implementation of suggested improvements authors found significant decrease in waiting times, rise in efficiency, and decrease of overtime hours. [2] proposed a flexible framework for modeling and simulation of inpatient health care. Authors offered a methodology which accommodates three types of view on health care system: process, resource, and organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…After implementation of suggested improvements authors found significant decrease in waiting times, rise in efficiency, and decrease of overtime hours. [2] proposed a flexible framework for modeling and simulation of inpatient health care. Authors offered a methodology which accommodates three types of view on health care system: process, resource, and organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, discrete-event simulation (DES) has been widely used in the literature to model and assess the performance of health-care systems (Jun, Jacobson, and Swisher 1999;Augusto and Xie 2006;Augusto and Xie 2014). However, except in Pehlivan, Augusto, and Xie (2013), DES has not been used jointly with MDP analysis to assess the validity of theoretical models under many assumptions.…”
Section: Prodel Augusto and Xiementioning
confidence: 98%
“…This paper recognizes that patients with different acuities have different needs, addressed by different step sequences, and using many kinds of resources, all of whose schedules affect lag times. Short-term planning and scheduling using Petri nets and DES [1] similarly lacks the intricate details of the healthcare process our models capture, such as work shifts, patient handoffs. Similarly, while UML modeling with discrete-timed Petri nets can guide optimization to determine the minimum required resources, and simulation can then evaluate EDs [11], unlike our approach, this method does not consider the complex constraints and policies of resource utilization.…”
Section: Related Workmentioning
confidence: 99%